2017
DOI: 10.3389/fimmu.2017.00927
|View full text |Cite
|
Sign up to set email alerts
|

CANDLE Syndrome As a Paradigm of Proteasome-Related Autoinflammation

Abstract: CANDLE syndrome (Chronic Atypical Neutrophilic Dermatosis with Lipodystrophy and Elevated temperature) is a rare, genetic autoinflammatory disease due to abnormal functioning of the multicatalytic system proteasome–immunoproteasome. Several recessive mutations in different protein subunits of this system, located in one single subunit (monogenic, homozygous, or compound heterozygous) or in two different ones (digenic and compound heterozygous), cause variable defects in catalytic activity of the proteasome–imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
88
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(91 citation statements)
references
References 42 publications
(101 reference statements)
0
88
0
3
Order By: Relevance
“…Normally, formation of the immunoproteasome is mainly induced by interferons to keep up with the increased demand of catalytic activity within the cell 148 . The assembly and maturation of these multiprotein structures are governed by facilitating proteins such as the proteasome maturation protein (POMP).…”
Section: Primary Immunodeficiencies Caused By Immunological Gain‐of‐fmentioning
confidence: 99%
See 1 more Smart Citation
“…Normally, formation of the immunoproteasome is mainly induced by interferons to keep up with the increased demand of catalytic activity within the cell 148 . The assembly and maturation of these multiprotein structures are governed by facilitating proteins such as the proteasome maturation protein (POMP).…”
Section: Primary Immunodeficiencies Caused By Immunological Gain‐of‐fmentioning
confidence: 99%
“…The combination of autoinflammation, autoimmunity, and immunodeficiency poses difficulties for treatment. Oral corticosteroids and methotrexate have provided some improvement, but etanercept (anti‐TNF‐α), anakinra (anti‐IL‐1), tocilizumab (anti‐IL‐6), and calcineurin inhibitors were shown to be ineffective 148,150 . Recently, multiple studies have reported that treatment with the JAK inhibitor baricitinib in CANDLE patients leads to remarkable amelioration of clinical severity scores and systemic inflammation 159‐162 …”
Section: Primary Immunodeficiencies Caused By Immunological Gain‐of‐fmentioning
confidence: 99%
“…Мутации в вышеописанных генах, а также редкие мутации в генах SAMHD1, ADAR1, IFIH1, результатом которых является гиперпродукция ИФН I типа, описаны не только при различных вариантах синдрома Айкарди-Гутьереса, но и у больных с ненаследственными формами СКВ, а также в связи с интерферонопатиями -широким спектром заболеваний со множественными аутоиммунными проявлениями [20]. Мутация в гене NEIL3 -фермента, участвующего в репарации ДНК, -обнаружена в семье с историей близкородственных браков, у сибсов с рецидивирующими респираторными инфекциями, иммунной цитопенией и нарушением аутотолерантности В-клеток [21].…”
Section: ифн I типа и дефекты внутриклеточной утилизацииunclassified
“…Indeed, rare mutations in the immunoproteasome PSMB8 gene have been identified in severe autoinflammatory disorders [89][90][91][92][93] . Moreover, recent studies have identified recessive mutations of immunoproteasome and proteasome genes resulting in altered proteolytic activity of the proteasome and sustained production of type 1 interferons in patients with the rare, genetic autoinflammatory CANDLE syndrome (Chronic Atypical Neutrophilic Dermatosis with Lipodystrophy and Elevated temperature) 94 . Taken together these data suggest that the absence or mutation of immunoproteasome subunits contributes to the onset of autoinflammatory and autoimmune diseases.…”
Section: Ups In Autoimmunitymentioning
confidence: 99%